Can a web-based community of practice be established and operated to lead falls prevention activity in residential care? - Francis-Coad, J.; Etherton-Beer, C.; Bulsara, C.; Nobre, D.; Hill, Anne-Marie (Mosby, Inc., 2016)
The aims of this study were to evaluate establishing and operating a web-based community of practice (CoP) to lead falls prevention in a residential aged care (RAC) setting. A mixed methods evaluation was conducted in two phases using a survey and transcripts from interactive electronic sources. Nurses and allied health staff (n = 20) with an interest in falls prevention representing 13 sites of an RAC organization participated. In Phase 1, the CoP was developed, and the establishment of its structure and composition was evaluated using determinants of success reported in the literature. In Phase 2, all participants interacted using the web, but frequency of engagement by any participant was low. Participatory barriers, including competing demands from other tasks and low levels of knowledge about information communication technology (ICT) applications, were identified by CoP members. A web-based CoP can be established and operated across multiple RAC sites if RAC management support dedicated time for web-based participation and staff are given web-based training.